Family Support Tidak Mempengaruhi Tingkat Keparahan Preeklampsia Pada Ibu Hamil - Istioningsih Istioningsih; Rina Anggraeni; Hendra Adi Prasetya (Jurnal Ilmu Keperawatan Maternitas, 2019)
Maternal Mortality Rate (MMR) in Indonesia has increased and is still a national probem because it is far from the SDG’s target. This is caused by the incidence of pregnancy hypertension including preeclmpsia. Family has an important role to influence the health status of its members. The purpose of this study was to identify the existence of a family support with preeclampsia severity. This study a case control design using consecutive sampling with 80 respondents in Kendal, Central Java. Family support data collection using Preceivec Social Support Family Scale (PSS-Fa) instrument. The result of this study there is no relationship between Family Support and Preeclampsia severity with p-value 0,892. Future research can specify the type of support so it is not general and in-depth.